Reverse Engineering of Dicing Blade to Prolong its Lifetime - Hishamuddin, Mas Izaty; Nayan, Nafarizal (Evolution in Electrical and Electronic Engineering, 2020)
This paper presents a study on the TiAlN hard coating was deposited on the existing dicing blade with the PVD technique using RF and DC magnetron sputtering. The surface morphologies of the dicing blade were analyzed by field emission scanning electron microscopy (FESEM) and material properties were investigated by using energy dispersive spectroscopy (EDS). The nanoindentation parameters such as hardness and Young’s modulus were investigated by nanoindenter (Hysitron Ti Premier) testing to characterize the hard coating on the dicing blade. The result shows the material properties of the dicing blade were nickel bond diamond dicing blade and the corresponding hardness of existing dicing blade measured by nanoindentation is around 2.83 GPa